Independent determinants of periodontitis in Yemeni adults: A case-control study - Al-Alimi, Abdulrahman; Halboub, Esam; Al-Sharabi, Ali Kaid; Taiyeb-Ali, Tara Bai; Jaafar, Nasruddin; Al-Hebshi, Nezar Noor (Wiley, 2018)
Objectives: The relative importance of risk factors of periodontitis varies from one population to another. In this study, we sought to identify independent risk factors of periodontitis in a Yemeni population. Methods: One hundred and fifty periodontitis cases and 150 healthy controls, all Yemeni adults 30-60 years old, were recruited. Sociodemographic data and history of oral hygiene practices and oral habits were obtained. Plaque index (PI) was measured on index teeth. Periodontal health status was assessed using Community Periodontal Index (CPI) and Clinical Attachment Loss (CAL) according to WHO. Periodontitis was defined as having one or more sextants with a CPI score ≥ 3. Multiple logistic regression modelling was employed to identify distal, intermediate and proximal determinants of periodontitis, while ordinal regression was used to identify those of CAL scores. Results: In logistic regression, PI score was associated with the highest odds of periodontitis (OR = 82.9) followed by cigarette smoking (OR = 12.8), water pipe smoking (OR = 10.2), male gender (OR = 3.4) and age (OR = 1.19); on the other hand, regular visits to the dentist (OR = 0.05), higher level of education (OR = 0.37) and daily dental flossing (OR = 0.95) were associated with lower odds. Somewhat similar associations were seen for CAL scores (ordinal regression); however, qat chewing was identified as an additional determinant (OR = 4.69). Conclusion: Water pipe smoking is identified as a risk factor of periodontitis in this cohort in addition to globally known risk factors. Adjusted effect of qat chewing is limited to CAL scores, suggestive of association with recession.